2006
DOI: 10.1182/blood-2006-06-030411
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo arterial differentiation of human multipotent adult progenitor cells

Abstract: IntroductionThe vascular system is a bipolar complex network of arteries that transport oxygen-rich blood to all tissues and veins that bring oxygendeprived blood back to the heart. 1 Because of this bipolar set-up, arteries and veins feature anatomic and physiological differences. Unlike venous endothelium, arterial endothelium is surrounded by several layers of smooth muscle cells (SMCs), separated by elastic laminae, and embedded in a thick layer of fibrillar collagen. 2 Moreover, both vessel types have a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 61 publications
(91 reference statements)
4
72
0
Order By: Relevance
“…GFP + mBMCs were isolated from the femurs, depleted of erythrocytes, washed, and transplanted. hMAPCs were established at the University of Navarra using BM from donors age 18-54, as described previously (46). Samples were obtained after informed consent was received from the donors according to guidelines of the Committee on the Use of Human Subjects in Research at the Clínica Universitaria, Pamplona.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GFP + mBMCs were isolated from the femurs, depleted of erythrocytes, washed, and transplanted. hMAPCs were established at the University of Navarra using BM from donors age 18-54, as described previously (46). Samples were obtained after informed consent was received from the donors according to guidelines of the Committee on the Use of Human Subjects in Research at the Clínica Universitaria, Pamplona.…”
Section: Methodsmentioning
confidence: 99%
“…For all stainings and analyses, 7-μm sections were used, spanning a muscle area of approximately 2 mm in thickness. H&E and Sirius red stainings were performed as described previously (46). For immunohistochemistry and immunofluorescence, a list of primary antibodies is provided as supplemental information (Supplemental Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Smooth muscle, skeletal muscle, and endothelial differentiation assays, as well as the in vitro and in vivo Matrigel assays were performed as previously described [14,23,27]. A detailed protocol of all differentiation and functional assays can be found in Supporting Information.…”
Section: In Vitro Differentiation and Functional Assaysmentioning
confidence: 99%
“…Even though hMAPCs are, like hMSCs and hMab, expanded adherent to culture vessels, differences in cell surface phenotype, expansion, and differentiation ability exist. For instance, hMAPCs can be expanded for more protracted periods of time than hMSCs and differentiate in vitro not only into mesenchymal cell types, but also into endothelial cells and cells with hepatocyte-like features [21][22][23][24]. Like hMSCs, hMAPCs have also significant trophic effects when grafted in vivo [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators reported the isolation of a different BM-derived multipotent cell type that displays a vast expansion capacity combined with a broad differentiation potential that encompasses cells from the three embryonic germ layers. 107 These multipotent adult progenitor cells (MAPC) are morphologically, molecularly, and functionally different from BM-MSC and can in vitro differentiate into EC that contribute to vasculogenesis in vivo [108][109][110][111] ( Table 1). Although MAPC represent an almost inexhaustible source of cells that can be used in STE vascularization, the longterm procedure required to derive MAPC makes an autologous approach unfeasible.…”
mentioning
confidence: 99%